Remoção de óleo da água produzida por adsorção: estudo de adsorventes, comparação entre processos e proposição de aumento de escala - Araújo, Dimitri Albuquerque (2017)
Nowadays, many residues were generated, from oil and gas production and exploration activities, like produced water. This water needs to be discarded or injected (EOR) according to limits established by environmental laws. In this work, the adsorptive capacity of sugarcane bagasse and commercial activated carbon in emulsified oil removal in produced water was studied, investigating batch operation, continuous contact in fixed bed column and scaleup procedure. The internal morphology and organization of the bagasse were verified by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The adsorbent porous structure by N2 adsorption at 77 K was obtained. Microporous area, external surface area, pore diameter and micropores volume were obtained from BET and Langmuir methodology. The methodology for detection of oil content was not able to quantify the oil remaining in tests involving bagasse. For activated carbon, adsorption isotherm obtained at 25 ºC in finite bath was statistically significant for the Freundlich model and indicated a favorable adsorptive process. The initial oil concentration in produced water was 228 mg/L. The Breakthrough curve was obtained through experiments carried out in a glass column of 3.2 cm internal diameter and activated carbon mass of 8.0068 g, reaching a fast adsorbent saturation. The results showed a continuous oil removal capacity of 90%. A good fit for Thomas and Yoon-Nelson models were observed. For the same organic load, batch process in one stirred tank needed 9 times more activated carbon than the continuous process. For two tanks in series, batch process needed 4.4 times more adsorbent. From breakthrough volume, VRUP = 13.5 L, and column exhaustion volume, VEXA = 15.5 L, could be calculated the fraction of capacity left unused bed (LUB = 12.9 %), the adsorptive capacity demonstrated by column (qCOL = 442.34 mg/g) and the total amount of effluent that can be treated per day in laboratory scale (VLAB = 209.1 L/day). Thus, the best scaleup propose for a efluente filtration rate constant of 1000 L/day was keeping constant the superficial velocity and taking the ratio height of the bed-column diameter equal to 20. Then, the column had 7 cm diameter, 140 cm of bed height, breakthrough time of 4.69 days and a activated carbono rate consumption of 0.58 kg/day.